Compliance with the good storage practices manual of a specialized drug warehouse of a Regional Health Directorate - Villaizan-Beraun, Jackelyn Isabel (2025)
Objective: To determine the level of compliance with GSP in the Specialized Drug Storage (SDW) of the Regional Health Directorate (DIRESA). Methods: Observational descriptive cross-sectional study. The national guidelines approved by DIGEMID for GSP inspection were used. The UPCH IRB and DIRESA reviewed and approved the study. Information was collected through direct verification and applying questions on the 9 components of the GSP.